2011
DOI: 10.1039/c1dt11130b
|View full text |Cite
|
Sign up to set email alerts
|

Six new metal–organic frameworks with multi-carboxylic acids and imidazole-based spacers: syntheses, structures and properties

Abstract: Six new metal-organic frameworks [Cu(obba)(bimb)·(obbaH(2))](n) (1), [Cu(obba)(bimb)](n) (2), [Zn(2)(obba)(2)(bimb)(2)(DMF)(2)(H(2)O)(3.5)](n) (3), [Ni(3)(2,2',4,4'-bptcH)(2)(bimb)(2)(H(2)O)(2)·(H(2)O)(2)](n) (4), [Ni(2)(bimb)(3)(H(2)O)(6)·(aobtc)·(DMF)(2)·(H(2)O)(2)](n) (5) and [Cd(3,3',4,4'-bptcH(2))(H(2)O)·(bimb)](n) (6), were obtained by reactions of 4,4'-bis(1-imidazolyl)biphenyl (bimb) and multi-carboxylic acids of 4,4'-oxybis(benzoic acid) (obbaH(2)), 2,2',4,4'-biphenyltetracarboxylate acid (2,2',4,4'-b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
19
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(23 citation statements)
references
References 71 publications
2
19
0
Order By: Relevance
“…Theoretical investigation on charge transfer and NLO response of Lindqvist type POMs (hexamolybdate/molybdate anions) functionalized with side chains organic ligands showed that the charge transfer from molybdate central core to the ligands has a central role in the enhancement of the SHG and significant values of second-order polarizability can be obtained in such configuration. [316,317] In the same way, metal polycarboxylates [312,[318][319][320][321] based crystals have shown promising potentialities in terms of second harmonic generation. E. Cariati and co-workers reported several complexes using trans-4-(4-dimethylaminostyryl) - [320] In this case, the very large SHG is mostly explained by the important quadratic polarizability of the ligands DAMS + (much more important than the SHG from the metal-to-ligand charge transfers contribution) combined with their self-organization in a layered structure with an optimized J-type aggregate configuration (Figure 28).…”
Section: Coordination and Organometallic Compounds Based Hybrid Systemsmentioning
confidence: 99%
“…Theoretical investigation on charge transfer and NLO response of Lindqvist type POMs (hexamolybdate/molybdate anions) functionalized with side chains organic ligands showed that the charge transfer from molybdate central core to the ligands has a central role in the enhancement of the SHG and significant values of second-order polarizability can be obtained in such configuration. [316,317] In the same way, metal polycarboxylates [312,[318][319][320][321] based crystals have shown promising potentialities in terms of second harmonic generation. E. Cariati and co-workers reported several complexes using trans-4-(4-dimethylaminostyryl) - [320] In this case, the very large SHG is mostly explained by the important quadratic polarizability of the ligands DAMS + (much more important than the SHG from the metal-to-ligand charge transfers contribution) combined with their self-organization in a layered structure with an optimized J-type aggregate configuration (Figure 28).…”
Section: Coordination and Organometallic Compounds Based Hybrid Systemsmentioning
confidence: 99%
“…In 1998, aw ide range of interpenetrating frameworks were reported by Batten and Robson. [33] Nevertheless, it is still ac hallenge for us to constructi nterpenetrating networks with novel topology.A sf ar as we know,m ost topology types of sixfold interpenetrating networks reporteda re of either the dia net or chiral net, [34][35][36][37][38][39][40][41] as well as af ew other nets, such as cdl; [42] pts, [43] honeycomb [44] and helical net. [45] Moreover,a lthoughm any sqc networks have been obtained, most of them are three-fold or without interpenetration [46] .H owever,t ot he best of our knowledge, there is no report on six-fold interpenetration with the topology of sqc6.C ompared with the other structures, compound 1 reveals au nique six-foldi nterpenetration with an unusual[ 2 + +2+ +2] mode.…”
mentioning
confidence: 99%
“…NMOFs are characterized with better dispersive nature than the micsron scale MOFs and they can easily sense small molecules with no loss in their intrigue framework architectures and topologies (Wang et al, 2011a(Wang et al, , 2011b. NMOFs with Eu(III), Zn(II) and Cd (II) as metal ion units have been reported for the detection of nitro aromatic compounds, small molecules and explosives (Kumar et al, 2014b;Wang et al, 2011aWang et al, , 2011bLi et al, 2008;Pramanik et al, 2011). Availability of pendent functional groups on some NMOF structures may be utilized to tag them with biomolecules such as nucleic acid, protein, antibody and enzymes (DeKrafft et al, 2009;McKinlay et al, 2010).…”
Section: Introductionmentioning
confidence: 99%